2016
DOI: 10.1002/btpr.2340
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ferroplasma acidiphilum growing in pure and mixed culture with Leptospirillum ferriphilum

Abstract: Biomining is defined as biotechnology for metal recovery from minerals, and is promoted by the concerted effort of a consortium of acidophile prokaryotes, comprised of members of the Bacteria and Archaea domains. Ferroplasma acidiphilum and Leptospirillum ferriphilum are the dominant species in extremely acid environments and have great use in bioleaching applications; however, the role of each species in this consortia is still a subject of research. The hypothesis of this work is that F. acidiphilum uses the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…A similar pattern of synergistic interaction between F. acidiphilum and L. ferriphilum was also observed [58]. The growth of chemomixotrophic F. acidiphilum was favored by the supernatant of chemolithoautotrophic L. ferriphilum, containing additional sources of the organic carbon (EPS and lysed cells) and vice versa, probably due to detoxification of the medium from organic compounds by mixotrophic F. acidiphilum and extracellular proteins of its "secretome" [58]. The study of the microbial community dynamics in various industrial processes of tank or heap biooxidation showed the dominance of the Ferroplasmaceae family members [59][60][61].…”
Section: Microbialsupporting
confidence: 75%
See 1 more Smart Citation
“…A similar pattern of synergistic interaction between F. acidiphilum and L. ferriphilum was also observed [58]. The growth of chemomixotrophic F. acidiphilum was favored by the supernatant of chemolithoautotrophic L. ferriphilum, containing additional sources of the organic carbon (EPS and lysed cells) and vice versa, probably due to detoxification of the medium from organic compounds by mixotrophic F. acidiphilum and extracellular proteins of its "secretome" [58]. The study of the microbial community dynamics in various industrial processes of tank or heap biooxidation showed the dominance of the Ferroplasmaceae family members [59][60][61].…”
Section: Microbialsupporting
confidence: 75%
“…Acidiphilum acidophilum was able to increase the efficiency of metal bioleaching due to the utilization of organic substances, therefore decreasing the toxicity of the culture medium for autotrophic acidophiles [57]. A similar pattern of synergistic interaction between F. acidiphilum and L. ferriphilum was also observed [58]. The growth of chemomixotrophic F. acidiphilum was favored by the supernatant of chemolithoautotrophic L. ferriphilum, containing additional sources of the organic carbon (EPS and lysed cells) and vice versa, probably due to detoxification of the medium from organic compounds by mixotrophic F. acidiphilum and extracellular proteins of its "secretome" [58].…”
Section: Microbialmentioning
confidence: 56%
“…acid mine drainage (Merino et al., 2015). This symbiotic association helps in oxidizing iron and sulfur containing minerals (Merino et al., 2016, 2015). A metabolic model for a mixed culture composed of L. ferriphilum and F. acidiphilum was reconstructed for deeper understanding of the metabolism of these microorganisms growing together (Merino et al., 2015).…”
Section: Microbial Consortia In Natural Systemsmentioning
confidence: 99%
“…A metabolic model for a mixed culture composed of L. ferriphilum and F. acidiphilum was reconstructed for deeper understanding of the metabolism of these microorganisms growing together (Merino et al., 2015). Further validation of the model revealed that F. acidiphilum utilizes the organic matter secreted by L. ferriphilum for growth, maintaining low levels of organic compounds in the culture medium and preventing their toxic effects on L. ferriphilum (Merino et al., 2016).…”
Section: Microbial Consortia In Natural Systemsmentioning
confidence: 99%
“…La comunidad AL original y los consorcios litótrofos acidófilos resistentes obtenidos a partir de ella tuvieron al género Acidithiobacillus (representado principalmente por el ASV 6) como dominante, con la excepción del consorcio resistente a cobre en el que predominó Ferroplasma (ASV 3), éste también fue dominante en el consorcio no expuesto y estuvo presente en el consorcio resistente a níquel. La presencia de Acidithiobacillus en ambientes acidófilos y de alta carga metálica es ampliamente conocida (Huang et al, 2016;Nuñez et al, 2016Nuñez et al, , 2017; de igual manera, las arqueas del género Ferroplasma también han sido reportadas en ambientes similares y su resistencia a cobre ha sido aprovechada para el desarrollo de procesos de biolixiviación de sulfuros minerales cuprosos como la calcopirita y la calcosina (Golyshina et al, 2000;Dopson et al, 2004;Golyshina & Timmis, 2005;Hawkes et al, 2006;Zhou et al, 2008;Merino et al, 2016).…”
Section: Discussionunclassified